2020
DOI: 10.1111/acel.13200
|View full text |Cite
|
Sign up to set email alerts
|

Targeting RAS‐converting enzyme 1 overcomes senescence and improves progeria‐like phenotypes of ZMPSTE24 deficiency

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Previous studies have reported that CAAX PTMs influence the protein levels of certain CAAX proteins, potentially by affecting protein turnover ( 28 , 30 , 31 ). Based on these reports, we evaluated the turnover rate of Ras2-CAAX variants using cycloheximide chase analysis ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that CAAX PTMs influence the protein levels of certain CAAX proteins, potentially by affecting protein turnover ( 28 , 30 , 31 ). Based on these reports, we evaluated the turnover rate of Ras2-CAAX variants using cycloheximide chase analysis ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, Lmna L648R/L648R mice like Zmpste24 −/− mice with two wild-type Lmna alleles express roughly equal amounts of prelamin A relative to lamin C, so this explanation seems unlikely ( 12 , 13 ). Another possibility is that the single amino acid substitution renders the L648R variant less “toxic” than native prelamin A, and determining whether binding of this variant to the known prelamin A interactors, such as AKT and SUN1 ( 44 46 ), is diminished would be of interest to test in the future. However, this explanation is difficult to reconcile with the wealth of data suggesting that it is the farnesyl and carboxylmethyl moieties of prelamin A that are primarily responsible for its adverse effects in cultured cells and mice ( 45 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that the single amino acid substitution renders the L648R variant less “toxic” than native prelamin A, and determining whether binding of this variant to the known prelamin A interactors, such as AKT and SUN1 ( 44 46 ), is diminished would be of interest to test in the future. However, this explanation is difficult to reconcile with the wealth of data suggesting that it is the farnesyl and carboxylmethyl moieties of prelamin A that are primarily responsible for its adverse effects in cultured cells and mice ( 45 47 ). Furthermore, mice engineered to express only a nonfarnesylated prelamin A, without any lamin C, develop cardiomyopathy but do not have progeroid phenotypes and live much longer and have less severe growth retardation than Zmpste24 −/− mice ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, these defensive responses might eventually aggravate health span and accelerate the aging process, even leading to frequent embryonic lethality ( 29 , 36 , 38 ). Furthermore, we and others ( 33 ) have shown that activation of Akt/mTOR signaling is supposed to protect Zmpste24-deficient embryos from development failure possibly induced by genomic instability ( 6 ) or defective mitosis ( 16 , 17 ) or to largely rescue Zmpste24-deficient aging phenotypes by targeting the lipid modification of prelamin A ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%